2021
DOI: 10.16965/ijar.2021.107
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and morphometric study of occipital condyles

Abstract: Introduction: The occipital condyles are undersurface protruberances of the occipital bone in vertebrates, which articulate with the superior facets of the atlas vertebra. The condyles are oval or reniform in shape, and their anterior extremities directed forward and medially and are closer together than the posterior end. Aim: The aim of the study is to provide important anatomical parameters for lateral transcondylar approach. Materials and Methods: 200 occipital condyles in 100 dry human skulls ( 73 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…A detailed knowledge of the morphology and morphometry of OC, as well as its relationship to the surrounding bony structures including the FM, the orifices of HC and the JF in dry skull was evaluated to provide essential data to improve surgical outcomes. The most prevalent shape of OC in this study was oval-like condyle or type I, which agreed with previous findings in Indians [ 14 , 19 , 26 ], and Turks [ 20 , 27 ]. In contrast, Aragão et al [ 13 ] and Bayat et al [ 28 ], reported that the most common shape in Brazilians was S-like condyle or type III and kidney-like condyle or type II in Iranians.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A detailed knowledge of the morphology and morphometry of OC, as well as its relationship to the surrounding bony structures including the FM, the orifices of HC and the JF in dry skull was evaluated to provide essential data to improve surgical outcomes. The most prevalent shape of OC in this study was oval-like condyle or type I, which agreed with previous findings in Indians [ 14 , 19 , 26 ], and Turks [ 20 , 27 ]. In contrast, Aragão et al [ 13 ] and Bayat et al [ 28 ], reported that the most common shape in Brazilians was S-like condyle or type III and kidney-like condyle or type II in Iranians.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the average OC-H was 7.4±1.1 mm, which was lesser than those reported previously [ 1 , 30 ]. This data can be used to determine how deep the OC must be drilled [ 14 ] and the successful insertion of screws during occipitocervical fixation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, removing the same amount of bone stock results in greater O-C1 joint instability in shorter condyles compared to longer ones, whereas a longer condyle may necessitate more widespread resection for optimum visualization (23,27,28). In addition, the thickness of OC also matters during condylectomy as one should know how deep of the OC must be drilled (21) . The greater thickness of OC may facilitate the successful screw placement during occipitocervical fixation (23).…”
Section: Chapter II Literature Review 1 the Anatomical Structure Of O...mentioning
confidence: 99%
“…A patient with a large OC has limited exposure to the ventral aspect of the CVJ (40). The height of the OC is also important during condylectomy because it is necessary to determine how deep the OC must be drilled (21). Furthermore, the higher thickness of OC may improve in the successful insertion of screws during occipitocervical fixation (23).…”
Section: The Prevalence Of Posterior Condylar Canal (Pcc)mentioning
confidence: 99%